THE WORMS COMPOST - EFFECTIVE FERTILIZER FOR IMPROVING DEGRADED SOILS - Larisa CREMENEAC; Tatiana BOCLACI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2013)
Management of organic waste is a difficult, complex and intractable in Moldova, according to international standards. Acute problem of organic matter from livestock sector waste is generated by storing them in unauthorized areas. Organic waste management strategies require different methods. One of them is organic waste bio conversion technology by worm’s cultivation. As the main natural wealth of the Republic of Moldova, soil requires a special care. Agriculture, in particular, should pay attention to the soil’s humus and nutrient status – and restore losses of humus and the nutrients used by crops. This requires measures to improve soil fertility. Land use provides, first of all return losses of humus and nutrients used by plants. Therefore measures required to improve soil fertility. The essence of the research was to highlight the role of worms compost improve the soil. To this end, in ETS "Maximovca" was organized an experiment that included three groups (two - experimental, to fund worms compost and one - control the natural background). Observations on soil fertility have been conducted over three years. The soil samples were collected by usual methods determined values of organic matter and humus. The results of the investigations, to determine the values of organic matter and humus samples collected from surface and depth 15 cm exceeded that of the sample control group to 29,7%; 11,4% and 34,3%; 37,1% in experimental group I and 9,3%; 11,6% and 45,5%; 45,5% in experimental group II. Therefore, worms compost embedded in a dose of 3-4 tons / ha during three years, has improved the fertility of the soil